The effects of international mergers and acquisitions on innovative financial performance for the higher education industry - Duane Frederick; Karina Kasztelnik (Journal of Business and Economic Studies (JBES), 2021)
Research indicates that 45% to 75% of mergers throughout all industrial sectors fail. The literature indicates increasing rates for higher education institution (HEIs) mergers. Researchers do not share common definitions of success for HEI mergers. One common and generally accepted definition for HEI success does exist through world class university ranking organizations lists of top HEIs. This study utilized WCU ranking criteria and found that HEIs are ranked based upon research strength, teaching quality, and global outlook to determine HEI rankings. This study adapted representative metrics used by these ranking organizations which served as the DVs in this study. The study adopted the Event Study theoretical framework to serve as the lens to evaluate the data and utilized a quantitative methodology with a causal-comparative research design. Data was obtained from the IPEDS database. The study utilized time as the within-subjects IV represented by Period 1 and Period 2 measures beginning the year of merger and 5 years subsequent to the merger. The between-subjects IV was merger status. The study sample included 80 HEIs which merged between 1988 - 2013 and 80 matching pair non-merging HEIs. The study used a two-way mixed design ANOVA to answer the following three research questions: "Are there interaction effects between time and merger status upon the DVs of revenues, fall enrollment rates, and nonresident alien rates?" The study found no statistically significant main effects between time and merger status upon revenues and nonresident alien rates and a statistically significant effect upon fall enrollment rates.
Keywords: 330; Merger; Acquisitions; Higher Education Institutions; Metrics; Event Study; Revenues; Fall Enrollment Rates; Nonresident Alien Rates; Metric Improvement